Free anteromedial thigh perforator flap: Complementing and completing the anterolateral thigh flap - Dushyant Jaiswal; Amol Ghalme; Prabha Yadav; Vinaykant Shankhdhar; Akshay Deshpande (Indian Journal of Plastic Surgery)
Objective: Theobjective of this study was to determine the indications, utility, advantages and surgical approach for the anteromedial thigh (AMT) flap. Materials and Methods: We reviewed the records of the patients in whom the AMT flap was used for head and neck reconstruction. We use an anterior approach to harvest the anterolateral thigh (ALT) flap with a non-committal straight line incision. This preserves both ALT and AMT flap territories intact, and further decision is based on the intraoperative anatomy of perforator and pedicle. The ALT flap was usually used as the first choice when available and suitable. Results: Free AMT skin flaps were harvested in 24 patients. All flaps were used for the head and neck reconstruction. Two flaps had marginal flap necrosis. One flap was lost due to venous thrombosis. Discussion: The thigh is an excellent donor site as it has large available skin territory, expendable lateral circumflex femoral artery system and low donorsite morbidity. The ALT flap is the most commonly used flap for reconstruction of soft-tissue defects. However, it is characterised by variable vascular pedicle and perforator anatomy. The AMT flap is an excellent alternative when the ALT flap is not available due to variable perforator anatomy, injury to perforator, when an intermediate thickness is needed between distal and proximal thigh or a chimeric flap is needed. Conclusion: The AMT flap offers all the advantages of the ALT flap without increasing donor-site morbidity. The anterior non-committal approach keeps both the ALT and the AMT flap options viable.